Response of Growth and Production of Butternut Squash (Cucurbita moschata) to Application of Mycorrhizae and Quail Manure - Aisar Novita; Miller Saputra Hasibuan; Efrida Lubis; Anggria Lestami; Bunga Raya Ketaren (Agrotechnology Research Journal, 2023)
The demand for butternut squash which continues to increase every year makes farmers try to increase their production, one of which is by applying biological and organic fertilizers. This study aims to determine the response of growth and production of butternut squash to the application of mycorrhiza and quail manure. This study used a randomized block design with 2 factors and 3 replications. The first factor was the application of mycorrhiza which consisted of 3 levels, namely: 0, 2.5, and 5 g/plant, while the second factor was quail manure which consisted of 4 levels, namely: 0, 1, 2 and 3 kg/plot. The results showed that the application of mycorrhizae had a significant effect on fruit length and fruit weight. The application of quail manure had a significant effect on increasing fruit weight. The interaction of mycorrhizae and quail manure did not significantly affect all observed parameters. Although it had no significant effect, the application of mycorrhiza and quail fertilizer was proven to increase the growth and production of butternut squash compared to the control (without the application of mycorrhiza and quail manure). The combination of mycorrhizal 2.5 g/plant and quail manure 1 kg/plot could increase butternut squash production.